Criminalization and prosecution of money laundering in Vietnam: addressing shortcomings to strengthen commitments with the European Union - Hoa Nguyen Thi Phuong (TalTech Journal of European Studies, 2025)
In 2023, Vietnam was added to the Financial Action Task Force and the European Union’s grey list due to specific deficiencies in its anti-money laundering framework, particularly in the criminalization and enforcement of money-laundering offences. This article undertakes a comparative analysis of Vietnam’s legal framework against international standards to identify existing limitations. Drawing upon statistical data and case studies, it examines the gaps in the prosecution of money-laundering offences. This research distinguishes itself by integrating European Union standards into the analysis, identifying previously unreported issues, while providing a comprehensive examination of the underlying causes of current challenges. Based on these insights, the paper proposes reforms to strengthen Vietnam’s criminalization and prosecution of money-laundering offences, thereby facilitating the country’s removal from the grey list.